2012
DOI: 10.1155/2012/503254
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Ultrasound in Resuscitation and the Rapid Ultrasound in Shock Protocol

Abstract: Assessment of hemodynamic status in a shock state remains a challenging issue in Emergency Medicine and Critical Care. As the use of invasive hemodynamic monitoring declines, bedside-focused ultrasound has become a valuable tool in the evaluation and management of patients in shock. No longer a means to simply evaluate organ anatomy, ultrasound has expanded to become a rapid and noninvasive method for the assessment of patient physiology. Clinicians caring for critical patients should strongly consider integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
19

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 85 publications
3
126
1
19
Order By: Relevance
“…Combining single ultrasonography analyses in a rapid multi-organ protocol improves accuracy of the diagnostic process in case of challenging clinical situations, like undifferentiated hypotension, sepsis and cardiac arrest. This potential was already introduced in some review articles and case series [2,8,9,12,14,37], but efficacy was also demonstrated by prospective studies [7,38]. On the basis of the recommendations of the main experts on point-of-care lung ultrasound [21], we added a pulmonary evaluation to a multi-organ ultrasonography protocol based on cardiac, veins and abdominal rapid examination of undifferentiated hypotension in emergency [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining single ultrasonography analyses in a rapid multi-organ protocol improves accuracy of the diagnostic process in case of challenging clinical situations, like undifferentiated hypotension, sepsis and cardiac arrest. This potential was already introduced in some review articles and case series [2,8,9,12,14,37], but efficacy was also demonstrated by prospective studies [7,38]. On the basis of the recommendations of the main experts on point-of-care lung ultrasound [21], we added a pulmonary evaluation to a multi-organ ultrasonography protocol based on cardiac, veins and abdominal rapid examination of undifferentiated hypotension in emergency [7].…”
Section: Discussionmentioning
confidence: 99%
“…Some protocols consisting in a goal-directed ultrasonography evaluation that integrate cardiac, abdominal and venous examination, have been already proposed and validated [7][8][9]. Some review articles already introduced the adjunct of a lung evaluation in the multi organ ultrasonography diagnostic procedure of undifferentiated hypotension and shock, but have not been validated by prospective studies on patients [10][11][12][13][14].…”
Section: Undifferentiated Hypotension Is a Common Condition In The Emmentioning
confidence: 99%
“…This E can help differentiate causes of hypotension, chest pain, and dyspnea and may aid in expediting condition-specific therapies. 3,25,26 There are multiple quantitative modalities for LVEF calculation; however, qualitative estimates of ejection fraction by EP FOCUS correlate well with both quantitative measurements and subjective estimates by cardiologists. 25,27 Qualitative assessment of global ejection is typically categorized as "hyperdynamic" (LVEF > 65%), "normal" (LVEF 50% to 65%), "moderately depressed" (LVEF 30% to 50%), or "severely depressed" (LVEF < 30%).…”
Section: Ejectionmentioning
confidence: 99%
“…9 This is in contrast with image and probe orientation utilized in traditional cardiologyperformed US, but has been recognized as an accepted convention that we find to be conceptually easier, particularly when performing EP FOCUS as part of an integrated examination such as the focused assessment with sonography for trauma (FAST) or the rapid US for shock and hypotension. 3,6 As has been discussed previously in the emergency US literature, EP FOCUS is not intended to replace comprehensive echocardiography (echo) when more thorough cardiology evaluation is indicated. The clinical questions addressed by EP FOCUS tend to be limited and qualitative but it should be understood that EP FOCUS findings may fall on a spectrum that can make binary categorization challenging.…”
Section: Approach To Exammentioning
confidence: 99%
See 1 more Smart Citation